2017
DOI: 10.1080/09639284.2017.1381033
|View full text |Cite
|
Sign up to set email alerts
|

How does contact with accountants influence perceptions of accounting?

Abstract: Contact with accountants has often been suggested as a strategy for changing the stereotypical perceptions people have of accounting. This study examines how contact with accountants influences these perceptions. The perceptions of sixteen people who have had no contact with accountants are compared with perceptions of sixteen people who have been the recipients of information from accountants. The perception data was collected by questionnaire and interview. Response data was analysed and compared between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
(77 reference statements)
0
14
0
3
Order By: Relevance
“…Tan and Laswad (2006) and Jackling and Keneley (2009) empirically tested the TRA's theoretical construct using samples from their respective countries and found that students seeking an accounting major were influenced by their interest in accounting and positive attitude toward studying accounting. The second stream of research has examined ways to improve accounting student' learning motivation and performance using several experiential techniques and materials that include: business simulation games and learning settings within the accounting course (Marriotte, 2004;Tanner and Lindquist, 1998); organizing direct contacts/mentoring with qualified accountants (Wells, 2013); and guest speakers (Metrejean et al, 2002). Physical activity in learning, while common in non-accounting disciplines, has not yet been tested in accounting education.…”
Section: Introductionmentioning
confidence: 99%
“…Tan and Laswad (2006) and Jackling and Keneley (2009) empirically tested the TRA's theoretical construct using samples from their respective countries and found that students seeking an accounting major were influenced by their interest in accounting and positive attitude toward studying accounting. The second stream of research has examined ways to improve accounting student' learning motivation and performance using several experiential techniques and materials that include: business simulation games and learning settings within the accounting course (Marriotte, 2004;Tanner and Lindquist, 1998); organizing direct contacts/mentoring with qualified accountants (Wells, 2013); and guest speakers (Metrejean et al, 2002). Physical activity in learning, while common in non-accounting disciplines, has not yet been tested in accounting education.…”
Section: Introductionmentioning
confidence: 99%
“…Richardson et al (2015) suggest that it is unclear whether the stereotype of accountants is a result of personal characteristics or the duties they perform. The negative perception of MAJ 36,5 accountants could be due to the complexity of the accountant¨s image, which is derived from the perceived personal characteristics of the accountant and of accounting tasks (Wells, 2019).…”
Section: Literature Review and Formulation Of Research Questions And Hypothesis 21 Stereotypementioning
confidence: 99%
“…According to Wells (2017), public perception of accounting has been overly concentrated in the technical role of accounting. However, a strong focus on quantitative tools and techniques is an inherent part of accounting to ensure objectivity in the process of accountability.…”
Section: Status Of Accountingmentioning
confidence: 99%